Sistem Absensi Harian Antititip Menggunakan QR Code Berubah Otomatis dan Verifikasi Foto untuk SMP Negeri 204 Jakarta - Yuma Akbar; Mesra Betty Yel; Joey Abdiner Parlindungan Hutabarat; Muhamad Fawaz Kamali; Rekardius Tafonao (Yayasan Kawanad, 2026)
Manual attendance management at SMP Negeri 204 Jakarta has proven to be inefficient and susceptible to data loss and damage. This study aims to develop and validate a QR Code-based attendance application called